2020
DOI: 10.30773/pi.2020.0264
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Performance on the Reading the Mind in the Eyes Test in First-Episode Psychosis and Clinical High Risk for Psychosis

Abstract: Objective Although previous studies have reported impaired performance in the reading the mind in the eyes test (RMET), which measures complex emotion recognition abilities, in patients with schizophrenia, reports regarding individuals at clinical high risk (CHR) for psychosis have been inconsistent, mainly due to the interacting confounding effects of general cognitive abilities and age. We compared RMET performances across first-episode psychosis (FEP) patients, CHR individuals, and healthy controls (HCs) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Behavioral results from the current study reinforce previous research on social cognitive deficits in SZ. We directly replicate past findings of reduced perceptual sensitivity and increased self-referential tendency during gaze perception in SZ 7,8 , as well as findings of reduced performance on the MSCEIT 11,76,77 , RME [78][79][80] , ER-40 69,80 , QCAE 81,82 , and SSPA 70,83 . In addition to replicating task-specific results, we extend previous work using latent variable modeling.…”
Section: Reinforcing and Extending Previous Social Cognition Researchsupporting
confidence: 85%
“…Behavioral results from the current study reinforce previous research on social cognitive deficits in SZ. We directly replicate past findings of reduced perceptual sensitivity and increased self-referential tendency during gaze perception in SZ 7,8 , as well as findings of reduced performance on the MSCEIT 11,76,77 , RME [78][79][80] , ER-40 69,80 , QCAE 81,82 , and SSPA 70,83 . In addition to replicating task-specific results, we extend previous work using latent variable modeling.…”
Section: Reinforcing and Extending Previous Social Cognition Researchsupporting
confidence: 85%
“…Therefore, stronger relationships between cognitive ToM and positive symptoms, as well as between affective ToM and negative symptoms is to be expected. However, there are studies that have found the opposite relationship; for example, Kim et al [ 25 ] performed a Pearson correlation analysis between ToM and clinical symptoms in 25 patients experiencing first-episode psychosis and found that affective ToM was associated with positive symptoms but not with negative symptoms; it is possible that this may be related to the greater severity of positive symptoms observed during early psychosis and the heterogeneity of the ToM paradigm employed. In fact, some other studies have not found such a relationship [ 9 , 20 ], reporting that ToM impairment in patients with SCZ has nothing to do with the severity of symptoms and that such defects are more likely to be a trait phenomenon rather than a state phenomenon, meaning that ToM impairment appears to be stable in those with SCZ and its high-risk groups and does not change as the symptoms do.…”
Section: Discussionmentioning
confidence: 99%